Polyfluoroalkyl substance exposure in the Mid-Ohio River Valley, 1991–2012. (September 2017) - Herrick, Robert L.; Buckholz, Jeanette; Biro, Frank M.; Calafat, Antonia M.; Ye, Xiaoyun; Xie, Changchun; Pinney, Susan M.
Abstract: Background: Industrial discharges of perfluorooctanoic acid (PFOA) to the Ohio River, contaminating water systems near Parkersburg, WV, were previously associated with nearby residents' serum PFOA concentrations above US general population medians. Ohio River PFOA concentrations downstream are elevated, suggesting Mid-Ohio River Valley residents are exposed through drinking water. Objectives: Quantify PFOA and 10 other per- and polyfluoroalkyl substances (PFAS) in Mid-Ohio River Valley resident sera collected between 1991 and 2013 and determine whether the Ohio River and Ohio River Aquifer are exposure sources. Methods: We measured eleven PFAS in 1608 sera from 931 participants. Serum PFOA concentration and water source associations were assessed using linear mixed-effects models. We estimated between-sample serum PFOA using one-compartment pharmacokinetics for participants with multiple samples. Results: In serum samples collected as early as 1991, PFOA (median = 7.6 ng/mL) was detected in 99.9% of sera; 47% had concentrations greater than US population 95th percentiles. Five other PFAS were detected in greater than 82% of samples; median other PFAS concentrations were similar to the US general population. Serum PFOA was significantly associated with water source, sampling year, age at sampling, tap water consumption, pregnancy, gravidity and breastfeeding. Serum PFOA was 40–60% lower with granular activated carbon (GAC) use. Repeated measurements and pharmacokinetics suggest serum PFOA peaked 2000–2006 for participants using water without GAC treatment; where GAC was used, serum PFOA concentrations decreased from 1991 to 2012. Conclusions: Mid-Ohio River Valley residents appear to have PFOA, but not other PFAS, serum concentrations above US population levels. Drinking water from the Ohio River and Ohio River Aquifer, primarily contaminated by industrial discharges 209–666 km upstream, is likely the primary exposure source. GAC treatment of drinking water mitigates, but does not eliminate, PFOA exposure. Graphical abstract: Highlights: First study of PFOA serum concentrations in the US in the early 1990s. Median PFOA concentrations were greater than the US population but decreased post 2000; other PFAS were similar to background. Using granular activated carbon in a drinking water treatment system reduces serum PFOA concentrations. Utilities with the Ohio River and Ohio River Aquifer as source waters are major PFOA exposure sources. PFOA discharges to the Ohio River 209–666 km upstream of the study area are the most likely source of PFOA. Abstract : In serum obtained from mid-Ohio River Valley residents (1991–2012), PFOA concentrations were elevated, and the absence of granular activated carbon water treatment modified the time of the peak levels.